2001
DOI: 10.1074/jbc.m100332200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Airway Epithelial Cell-specific Short Chain Alcohol Dehydrogenase/Reductase Gene Whose Expression Is Up-regulated by Retinoids and Is Involved in the Metabolism of Retinol

Abstract: Multiple retinoic acid responsive cDNAs were isolated from a high density cDNA microarray membrane, which was developed from a cDNA library of human tracheobronchial epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 56 publications
3
37
0
Order By: Relevance
“…Second, RDH expression levels can be regulated by key signaling pathways. In this respect, Li et al (32) have demonstrated dynamic regulation of estRDH levels in rat uterus during the estrous cycle, and Jette et al (21) have described transcriptional regulation of human hRDH-TBE/3␣-HSD/RDHL by APC and cdx2 (21,(32)(33)(34). Consistent with this, we have found that rdh1l expression levels decreased more than 3-fold in zebrafish carrying mutations in the APC tumor suppressor gene as compared with wild type animals.…”
Section: Fig 5 Apc Mutants Display Decreased Rdh1l Expression and Isupporting
confidence: 77%
“…Second, RDH expression levels can be regulated by key signaling pathways. In this respect, Li et al (32) have demonstrated dynamic regulation of estRDH levels in rat uterus during the estrous cycle, and Jette et al (21) have described transcriptional regulation of human hRDH-TBE/3␣-HSD/RDHL by APC and cdx2 (21,(32)(33)(34). Consistent with this, we have found that rdh1l expression levels decreased more than 3-fold in zebrafish carrying mutations in the APC tumor suppressor gene as compared with wild type animals.…”
Section: Fig 5 Apc Mutants Display Decreased Rdh1l Expression and Isupporting
confidence: 77%
“…2A). Although there are three potential splice variants of the RDHL gene (as deposited in GenBank TM , accession clones AF067174, AF240698, and AF240697), we confirmed by RT-PCR that normal colon expresses the isoform corresponding to clone AF067174 (data not shown), the same splice variant characterized as a retinol dehydrogenase (38). Expression of RDHL was low but also detectable in heart, spleen, placenta, and lung ( Fig.…”
Section: Retinol Dehydrogenases Are Down-regulated In Neoplasticmentioning
confidence: 48%
“…The first gene encoded RDH5, an enzyme that catalyzes the conversion of retinol into retinal. The second gene encoded RDHL, a recently described, novel retinol dehydrogenase (described by Soref et al (38), but referred to as hRDH-TBE). Each of these genes was downregulated at least 2-fold in ϳ70% of both adenoma and carcinoma tissues relative to normal (Fig.…”
Section: Retinol Dehydrogenases Are Down-regulated In Neoplasticmentioning
confidence: 99%
“…In our hands, human DHRS9 expressed in Sf9 cells and analyzed using DHRS9-enriched microsomal fraction has a negligible all-trans -or cis -retinol dehydrogenase activity in vitro ( 40 ), compared with similarly produced RoDH4 or RL-HSD ( 28,29 ). However, others have reported that human DHRS9 and its rat ortholog (SDR9C26) contribute to atRA production when expressed in transiently transfected, living COS cells or astrocytes incubated with 2 µM retinol ( 19,39 ). Surprisingly, silencing of rat DHRS9 expression in rat astrocytes leads to an increased rather than decreased conversion of retinol to atRA ( 19 ).…”
Section: Biosynthesis Of Atra From Retinolmentioning
confidence: 98%
“…A third member of the SDR9C family, DHRS9 (SDR9C4, also known as RDHL, 3 ␣ -HSD), has been implicated in atRA biosynthesis in humans ( 39 ). In our hands, human DHRS9 expressed in Sf9 cells and analyzed using DHRS9-enriched microsomal fraction has a negligible all-trans -or cis -retinol dehydrogenase activity in vitro ( 40 ), compared with similarly produced RoDH4 or RL-HSD ( 28,29 ).…”
Section: Biosynthesis Of Atra From Retinolmentioning
confidence: 99%